2020
DOI: 10.1016/j.scitotenv.2020.138147
|View full text |Cite
|
Sign up to set email alerts
|

Scaled outdoor experimental studies of urban thermal environment in street canyon models with various aspect ratios and thermal storage

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(38 citation statements)
references
References 84 publications
1
37
0
Order By: Relevance
“…Anthropogenic heat flux is closely related to the change in built-up area around the stations (Figure 1B). Therefore, anthropogenic heat flux can be considered to reliably reflect the effects of both anthropogenic emissions and land-use change related to latent heat flux and sensible heat flux (Jiang et al, 2019;Chen et al, 2020). Therefore, classified the stations by the mean anthropogenic heat fluxes around all the stations.…”
Section: Division and Matching Of Urban And Rural Stationsmentioning
confidence: 99%
“…Anthropogenic heat flux is closely related to the change in built-up area around the stations (Figure 1B). Therefore, anthropogenic heat flux can be considered to reliably reflect the effects of both anthropogenic emissions and land-use change related to latent heat flux and sensible heat flux (Jiang et al, 2019;Chen et al, 2020). Therefore, classified the stations by the mean anthropogenic heat fluxes around all the stations.…”
Section: Division and Matching Of Urban And Rural Stationsmentioning
confidence: 99%
“…In addition, urbanization is not only reflected by the two-dimensional horizontal urban expansion but also by the vertical morphology of the three-dimensional urban spatial structure. Previous studies suggested that the vertical geometry of urban canopy building also had an impact on local microclimate (Oke, 2004;Bonacquisti et al, 2006;Chen et al, 2020). In the future, we will expand three-dimensional indicators to supply the indicators of urbanization bias correction.…”
Section: Discussionmentioning
confidence: 98%
“…Urbanization directly affects the types of land use/cover and anthropogenic heat emissions around meteorological stations, leading to major changes in the observation environment (Gallo et al, 1996;Peterson, 2006;Trusilova et al, 2008;Chen et al, 2020), which in turn has an important impact on the accuracy, representativeness, and homogeneity of meteorological observation data (Davey and Sr, 2005;Vose, 2005). The contribution of the socalled urbanization bias (the effect of urbanization on surface air temperature (SAT), the list of abbreviations used in this article and their expanded names can be found in Appendix A) to meteorological observation data usually stems from changes in the observation environment against the background of urbanized areas (Ren et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The Ten mean annual zonation is characterized by a major inner land zone with temperature below 22 C and a costal and mountain zone with a temperature between 23 and 27 C. The hotter Ted in mountain and coastal zones in comparison to Ten is due to the proximity to the sea and the higher elevations that leads to a temperate air temperature environment. DTR is an essential element of the climate system and was used for urban thermal environment analysis, for example, extensive heat waves, heat-related health issues, landscaping and recreation, and engineering of heat transfer efficiency in buildings and roads (Duan et al 2014;Wang and Upreti 2019;Yang et al 2020;Chen et al 2020). The pattern of DTR closely resembles the pattern of Ted, where the mountains and coastal zones indicate cooler temperatures than the inner land zones.…”
Section: (A)mentioning
confidence: 99%